The Relationship between Body Image and Self-Esteem with the Tendency of Body Dysmorphic Disorder (BDD) Among Adolescents Using Social Media - Safitri, Nindya Ayu; Suroso; Pratitis, Niken Titi (Kirana Publisher (KNPub), 2025)
This study aims to analyze the relationship between Body Image and Self-Esteem with the tendency of Body Dysmorphic Disorder (BDD) among adolescents using social media. The study involved 115 respondents aged 16–18 who were active social media users. A quantitative method with multiple linear regression was employed. Results indicate a significant relationship between Body Image and Self-Esteem on BDD tendencies (F = 50.669; p < 0.05). Partially, Body Image showed a significant positive relationship with BDD tendencies (t = 8.468; p < 0.05), while Self-Esteem had a significant negative relationship (t = -2.652; p < 0.05). Body Image contributed 40.4%, and Self-Esteem contributed 7.1%, with a combined total contribution of 47.5%. These findings demonstrate that nearly half of the variability in BDD tendencies can be explained by Body Image and Self-Esteem. The study highlights the role of social media in exacerbating body perception and self-esteem issues, particularly through unrealistic beauty standards. This study suggests the importance of social media literacy, improving Self- Esteem, and promoting positive Body Image to reduce BDD risk among adolescents.